The Effect of Age on English Professors’ Integration of the New Technologies in Teaching - Hicham Laabidi (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2016)
The integration of computer technologies in teaching has become a vital technique to prepare students to face the challenges of the 21st century. Indeed, today’s education systems have moved from a focus on information transformation through books, blackboards and chalks  to a concentration on information processing via technological instruments, mainly computers, smart phones and tablets. Therefore, teachers are required to adopt these new technologies in their teaching practices. However, it is observed that there are several factors affecting teachers’ actual implementation of computer technology in different educational institutions. This paper aims to examine the impact of the age factor on English professors’ use of Information and Communication Technology (ICT) in Moroccan higher institutions. Descriptive analysis of means, and standard deviations were used to analyse the collected data. Also, inferential statistics, especially the ANOVA test, were employed to determine the impact of age on ICT adoptions. The findings revealed that there are statistically significant differences in the means of professors’ age when integrating ICT in instruction, F(3,159)=20.455,p<0.05.